Analisis Efektivitas Mesin CNC Lathe Berbasis Overall Equipment Effectiveness (OEE) - Firdaus, Hersa Ridwan; Ihsan, Tiaradia (Jurnal Sains dan Teknologi (JSIT), 2026)
The effectiveness of production machines is a key factor in increasing the productivity and competitiveness of the manufacturing industry. CNC Lathe machines as one of the main machines in the machining process are required to operate optimally with a high level of reliability and quality. This study aims to analyze the level of effectiveness of CNC Lathe machines using the Overall Equipment Effectiveness (OEE) method and identify the sources of production losses based on the Five Big Losses concept. The research method used is a quantitative approach with a case study on one CNC Lathe machine unit in a manufacturing company with a make-to-order production system. Research data were obtained through direct observation of machine working time, downtime, number of outputs, and the number of defective products during one production shift. The results showed that the availability value was 94.10%, performance was 98.28%, and quality was 99.50%, resulting in an OEE value of 92.01%. This value has exceeded the world-class standard of 85%, which indicates that the performance of the CNC Lathe machine is in the very good category. The Five Big Losses analysis shows that the dominant losses come from breakdown losses and idling and minor stoppages. This research contributes by evaluating the performance of a CNC lathe machine in a contextualized make-to-order production system and recommending improvements to maintain and enhance machine effectiveness.